Unveiling Environmental and Islamic Narratives in Avatar :The Way of Water": An Eco-Critical Analysis and AI-Driven Exploration - Juliastuti; Thayyib , Magfirah; Zamruddin, Mardliya Pratiwi (Journal of Language and Literature Studies, 2024)
"Avatar: The Way of Water" is a highly anticipated sequel in James Cameron's groundbreaking franchise, promising a deeper exploration of environmental themes intertwined with indigenous cultures. This study employs eco-critical analysis, augmented by AI insights, to investigate into the intricate connections between environmentalism and Islamic perspectives within the narrative. By examining the movie's portrayal of nature, spirituality, and socio-political dynamics, this study aims to uncover underlying themes that resonate with Islamic environmental ethics. Through the lens of AI-assisted analysis, the researchers unveil nuanced layers of interpretation, shedding light on the movie's potential to inspire meaningful dialogue on environmental stewardship and cultural sustainability. The researchers examine the symbiotic ecology and its hypothetical biology, which is proposed to be "better" than the metal-based technology used by the 'invading' humanity. It challenges the idealized notion of nature as a collection of native animals, plants, and people. Lastly, this study explores the different anthropocentric themes that the movie explores, criticizes the Na'vi's subtly "humanistic" domination over other fauna, and explores the prospects of embracing a truly impartial perspective to capture the realities of oppressed not humans.